ON STEREOTROPISM IN TENEBRIO LARVÆ - Crozier, W. J. (The Rockefeller University Press, 1924)
Larvæ of Tenebrio while creeping show homostrophic responses, and stereotropic orientation to lateral contacts. Homostrophic orientation is inhibited by stereotropism. Both depend upon the anterior portion of the central nervous system. Stereotropic orientation due to unilateral contact, particularly at the anterior end, persists briefly after the cessation of the contact. Equal posterior bilateral contact of the body obliterates stereotropic bending. Unequal posterior bilateral contacts lead to orientation through an angle roughly proportional to the differences in contact areas. Functional symmetry in such responses is not disturbed by asymmetrical distribution of the body "hairs." The stereotropic orientation undergoes reversal of direction, central in origin, when the stimulation is sufficiently intense. Stereotropic response, leading to maintained lateral contact with a surface or to bending when the end of such a surface has been passed, is inhibited by a definite intensity of light. These findings (1) round out the demonstration that stereotropism is truly of a tropistic character, and (2) make possible the understanding of conduct in a case involving the participation of contact stimulation, phototropism, temperature, and homostrophy.